Pengaruh Hubungan Kerja Kemanusiaan Terhadap Proses Pengambilan Keputusan (Satu studi pada Kantor Kecamatan malalayang Manado) - Raranta, Deky Bernad; Posumah, Jhonny Hanny; Tampi, Gustaf (Sam Ratulangi University, 2015)
As it known that human factors in administration (including management andorganization in the dynamic sense) holds a very important and decisive. The mostimportant and decisive, because other than humans have feelings and ratio as beingthe noblest of God's creation, is also a determinant factor, because of the